Realizing Recovery: the U.S. Substance Abuse and Mental Health Services Administration’s Efforts to Foster Social Inclusion - del Vecchio, Paolo; Nugent, Catherine; Townsend, Wilma; Torres, Ivette; Baker, Marsha (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2012)
For nearly 20 years, the U.S. Substance Abuse and Mental Health Services Administration (SAMHSA) has fostered social inclusion for Americans with mental and/or substance use disorders. SAMHSA has done this by promoting the recovery paradigm, an approach predicated on a positive, strength-based, and person-centered view of those with behavioral health conditions. SAMHSA has provided leadership by promoting policies, programs, practices, and public awareness initiatives that advance recovery, recovery support services, and recovery-oriented service delivery systems. SAMHSA’s approach has been participatory, engaging a variety of stakeholders, and comprehensive, focusing on multiple strategies in targeted priority areas.